PA6 Death chat: engaging with dying and death. Issue Volume 5: Issue (2015)Supplement 1 (1st April 2015) - Goodhead, Andrew; Hartley, Nigel
Abstract : Background: Talking about death continues to be a social taboo. St Christopher's has a large, welcoming social space, (The Anniversary Centre) and is committed to opening up its buildings in a number of ways. The St Christopher's social programme, of which Death Chat is part, aims to break down social taboos. Aims: Hospices have a responsibility to engage creatively with patients, family members, carers and the wider community. Death Chat, held in the hospice buildings, enables honest discussion about dying and death and topics surrounding these themes. Methods: Death Chat meets weekly and is an open meeting that takes a different subject each week as the starting point for conversation. Cheese and wine are shared and participants quickly find a place in the group. Results: Death Chat has attracted patients, family members, bereaved relatives and the community since September 2013. Attendees have reflected that coming has broken taboos. Peter said, 'it's nowhere near as depressing as it sounds; it's a nice, friendly atmosphere – a convivial place.' Molly found Death Chat to be a welcoming, open and challenging space, 'I have learnt that death is more about my attitude to life than anything else. It has been by far the most important lesson I have learnt since dealing with bereavement.' Conclusion: Death Chat provides a forum in which discussion of dying and death for recognises that these are social events and reclaims them from being taboo, to being a normal part of life's experience.